Exploring the impact of BMI and physical activity on caffeine use disorder and nutritional attitudes among adults in Türkiye - Orhan, Bekir Erhan; Alkasasbeh, Walaa Jumah; Karaçam, Aydin; Amawi, Adam Tawfiq; Canli, Umut (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to examine the relationship between caffeine use disorder and attitudes toward healthy nutrition in relation to individuals' body mass index (BMI) and physical activity levels. It also explored the influence of sociodemographic variables such as age, gender, marital status, and education level.MethodsData were collected from 509 adults who completed three instruments: the Caffeine Use Disorder Questionnaire (CUDQ), the Attitudes Scale for Healthy Nutrition (ASHN), and a demographic and behavioral survey. BMI was calculated from self-reported height and weight, and participants were classified according to WHO guidelines (underweight, normal, overweight, and obese). Physical activity level was self-reported and categorized as sedentary (0 days/week), low (1–2 days/week), moderate (3–4 days/week), and high (5+ days/week). Descriptive statistics, independent samples t-tests, one-way ANOVA, and Pearson correlation analyses were conducted using SPSS 25.ResultsStatistically significant differences were found in ASHN scores based on gender (p = 0.010), marital status (p < 0.001), education level (p < 0.001), BMI category (p < 0.001), and physical activity frequency (p < 0.001). Women and married individuals exhibited more positive emotional and behavioral nutrition attitudes. Higher education and physical activity levels were associated with improved attitudes across all ASHN subdimensions. CUDQ scores were higher among participants with high physical activity (p < 0.05) but significantly lower among those classified as obese (p < 0.001). Negative correlations were identified between CUDQ scores and ASHN total (r = −0.20), positive nutrition (r = −0.20), and malnutrition (r = −0.23).DiscussionThe findings highlight the role of demographic and lifestyle factors in shaping caffeine consumption patterns and nutritional attitudes. Public health strategies should consider these variables when developing dietary and stimulant-use interventions. Promoting healthy nutrition and responsible caffeine consumption particularly among physically active individuals may enhance long-term health and behavioral outcomes.